Design in offshore structures proceedings of a conference entitled "Development in the design and construction of offshore structures" organized by the Institution of Civil Engineers and held in London on 23-24 March 1983. (Thomas Telford, 1983)
Marine environment, design of platforms, and maintenance and repair are just some of the issues discussed in these papers from a conference on design in offshore structures.
Conference proceedings.
Keywords: Offshore structures -- Design and construction -- Congresses.; elektronické knihy; electronic books